The Problem of Social Protection in Albania - Shkreli Axhemi, Arlinda; Dragoshi, Gert (Comparative Economic Research. Central and Eastern Europe, 2013)
The aim of this paper is to analyze the social protection system in Albania during the last two decades. It highlights some of the problems and issues which are closely associated with elements of social security, as a phenomenon that focuses on finding solutions or solving the problems in social security systems in Albania. Of great importance are the changes in the social security legislation in recent years, which led to a new structure of the social insurance market in Albanian society. Also discussed are the types of benefits offered by our social insurance system. Our country occupies a special place in relation to the problems it has encountered with social protection and the social security law.